Projeto gráfico inclusivo para a elaboração do Guia multiformato sobre assistência estudantil da Universidade Federal do Rio Grande do Norte - Nascimento, Eriadne Teixeira do (2023)
This final paper has as its objective of research the graphic design of a multiformat guide about the actions and services related to student support at the Universidade Federal do Rio Grande do Norte (UFRN), using the inclusive design approach for it. The content of the guide is the object of the master’s degree by Ana Rita Rodrigues dos Santos, from the Graduate Program in Special Education at UFRN and her research consists of compiling informations in order to reduce communication noises. Thus, taking into account the diversity of the academic community, was observed the need for inclusive practices in accessing information. Like this, the general objective of this final paper consists in the elaboration of the graphic design for the UFRN Student support guide. For your production formats were envisaged that cater to the public with visually impairment, blind and low vision, as well as deaf and deafened. In order to reach the proposed objective, were used the methods proposed by Bonsiepe (1984) and Munari (1981) adapted in four major macro phases: 1) problematization; 2) research; 3) preliminary design and 4) final model. It is believed that the project achieved its essential requirements and that the method applied in conjunction with the public’s contribution to its development was of profound relevance to the result achieved.